English morphology for the language teaching profession - Bauer, Laurie, 1949-; Nation, I. S. P. (New York : Routledge, 2020)
'This highly accessible book presents an overview of English morphology for all those involved in the English-language teaching industry. For non-native learners, the ability to recognize and produce new words in appropriate circumstances is a challenging task, and knowledge of the word-building system of English is essential to effective language learning. This book clearly explains the morphology of English from the point of view of the non-native learner and shows how teachers and professors can instruct EFL students successfully with effective materials. Covering the scope of the task of teaching English morphology specifically to non-native learners of English, bestselling authors Bauer and Nation provide a range of strategies and tactics for straightforward instruction, and demonstrate how teachers of English as a foreign language can easily integrate learning of the morphological system into their language courses. This book helps teachers and learners make sensible decisions about where to focus deliberate attention, what to be careful about, and what not to be concerned about. It offers a range of shortcuts, tips and tricks for teaching, and gives detailed practical information on topics including: Sound and spelling Possessives Comparative and superlative Past tense and past participle Making nouns, verbs, adjectives, adverbs, words with prefixes Learned word-formation. This book is essential and practical reading for graduate students on English language teaching courses, preservice teachers, consultants, practitioners, researchers, and scholars in ELT'--
1. Learning English morphology -- 2. Assumptions -- 3. Sound and spelling -- 4. Plural of nouns -- 5. Possessives -- 6. Comparative and superlative -- 7. Third person singular -s -- 8. The -ing form of the verb -- 9. Past tense and past participle -- 10. Numbers -- 11. Compounds -- 12. Making nouns -- 13. Making verbs -- 14. Making adjectives -- 15. Making adverbs -- 16. Making words with prefixes -- 17. Making words without affixes -- 18. Learned word-formation -- 19. Morphology and frequency -- Reading and sources -- Indexes -- Index of affixes.
OCLC-licensed vendor bibliographic record.
Keywords: English language -- Morphology; English language -- Word formation